Effects of In2O3 nanoparticles doping on the photoluminescent properties of Eu2+/Eu3+ ions in silica glasses. Issue 1 (January 2019) - Chen, Ping; Mao, Yiwei; Hou, Shaodong; Chen, Yang; Liu, Xiaofen; Lou, Yang; Chen, Aichen; Yang, Luyun; Li, Jinyan; Dai, Nengli
Abstract: Eu 2+ /Eu 3+ ions doped silica glasses contained In2 O3 nanoparticles (NPs) have been fabricated by using nanoporous silica glasses. Interestingly, efficient energy transfer from In2 O3 NPs to Eu 2+ /Eu 3+ ions enhanced the photoluminescence (PL) emission of Eu 2+ /Eu 3+ ions, which derives from lattice defects in In2 O3 NPs. Our work has not only demonstrated a facile way to fabricate NPs and rare earth ions co-doped silica glasses, but also extended the applications of semiconductor oxide NPs such as In2 O3 NPs.